EU-ASEAN Cooperation In Facing Global Issues: Development and Pandemic - Fernandes, Mario; Samputra, Palupi Lindiasari (Budapest International Research and Critics University, 2021)
International cooperation between European Union (EU) and ASEAN is needed to deal with global issues related to Development and COVID-19 Pandemic. This study aims to see the implementation of liberalism and regionalism’s theoretical approach within the EU-ASEAN Cooperation’s framework. The qualitative method is used to answer the research objectives. The research data are obtained from the European Commission, ASEAN Secretary, Worldbank, WIPS, WHO, and UNCTAD to describe the EU-ASEAN cooperation. To deepen the desk study related to the themes, the author also conducted an analysis and construction of reports and news in print and online mass media related to the ASEAN European Union Cooperation in the development of the COVID-19 Pandemic during the 2016-2021 period. For development issues, the data used are from 2016 to 2021, meanwhile, for COVID-19 Pandemic issues, the data used are from 2020 to 2021. The results show that EU-ASEAN cooperation is more integrated regarding global issues. It is proven by the existence of many collaborations within the framework of Development Cooperation and Cooperation in overcoming the COVID-19 Pandemic. In addition, the flow of globalization also facilitates cooperation between the EU and ASEAN. This proves that the existence of the European Union and ASEAN, as well as their relationship based on Liberalism Theory in international relations, shows that there are no boundaries between countries in conducting international cooperation. The goal that wants to be achieved is to fight for common or global interests.